EP-364 The new normal in the post-pandemic world: Our experience of organising a three-part webinar series for the CST 2022 Applicants. (9th August 2022) - Rahman, Atiqur; Badawi, Marwa; Swamad, Mohamed; Ali, Ramla; Vincent, Elizabeth; Sharp, Elizabeth
Abstract: Introduction: In the time of COVID-19, the influx in the use of the online platform has been paramount. The surgical world is no exception with the first virtual selection process for Core Surgical Training (CST) 2021 applicants. We, the current core trainees from the Kent, Surrey and Sussex (KSS) deanery organised this three-part webinar series for CST 2022 applicants to aid our future colleagues. Materials and Methods: The event poster was circulated among the surgical tutors, medical education department across the KSS region, all the foundation schools and to Foundation Trainees Surgical Societies (FTSS) across the UK. It was advertised on Facebook, Twitter, WhatsApp and Eventbrite. Google Workspace was used to manage registered participants and Microsoft Teams were used for the webinars. Discussion: A total of 526 participants registered. 69.9% of them registered through social media whereas 16.4% and 9.8% through the medical education department and word of mouth respectively. The first part covering the CST program overview and self-assessment guidance was attended by 96 of them on 16 November 2021. The second part covering interview stations was attended by 29 participants on 14 December 2021. We received positive feedback from 42 and 8 participants following each webinar respectively. We currently have 88 participants registered for our mock interview sessions planned for late January 2022. Conclusions: The virtual selection process is here to stay. Well-organised events like this will help the candidates prepare well for their interview as well as helping the current trainees with their teamwork, leadership and organisation skills.